The effect of epigallocatechin gallate on hepatocytes isolated from normal and partially hepatectomized rats - Mezera, Vojtech; Kucera, Otto; Moravcova, Alena; Peterova, Eva; Cervinkova, Zuzana (Canadian journal of physiology and pharmacology, 2014)
Epigallocatechin gallate (EGCG) is an antioxidant found in green tea. In this study, male Wistar rats were subjected either to partial hepatectomy (PHx), or a sham operation (LAP). Twenty-four hours after surgery, hepatocytes were isolated and treated with various concentrations of EGCG for up to 72 h. We then measured markers of cell viability, oxidative stress, DNA synthesis, and caspase activity. Morphological criteria, cell viability tests, and albumin synthesis revealed toxicity starting at 10 μmol/L. DNA synthesis was higher in hepatocytes isolated from rats after PHx and inhibited by EGCG. Furthermore, EGCG increased the activity of caspases 3 and 7, seen more in hepatocytes from PHx rats. In conclusion, EGCG at a concentration of 10 μmol/L was toxic for hepatocytes isolated from both PHx and LAP rats.
Keywords: hepatectomy; antioxydants; Dose-Response Relationship, Drug; katechin; Hepatocytes; vztah mezi dávkou a účinkem léčiva; Rats; primary cell culture; apoptose; Antioxidants; Primary Cell Culture; DNA; kaspasa 3; epigallocatechin gallate; Rats, Wistar; mužské pohlaví; antioxidants; culture cellulaire primaire; hepatektomie; Oxidative Stress; primární buněčná kultura; Hepatectomy; krysa rodu Rattus; antioxidancia; kaspasa 7; stress oxydatif; hepatocyty; Catechin; hépatocytes; hépatectomie; oxidative stress; zvířata; Caspase 3; catechin; Caspase 7; viabilita buněk; Cell Survival; catéchine; potkani Wistar; oxidační stres; hepatocytes; liver regeneration; apoptosis; régénération du foie; le gallate d’épigallocatéchine; Male; Animals